UPAYA PENCEGAHAN PEREDARAN NARKOBA BAGI ABK MELALUI PROGRAM “SADAR BERNYALI” BERBASIS AKSI “GOSOK” DI SLBN 1 MATARAM TAHUN 2018 - Wulan, Arifah Sucining (Jurnal Ilmiah Widya Pustaka Pendidikan, 2021)
Abstract Increasing awareness to care about the influence of drug trafficking in the special needs school environment needs special attention. Through activities that are preventive in nature in the form of the” sadar bernyali” based on “gosok” action program., which aims as an effort to prevent an recognize the dangers of drugs and to build courage of all school members to take the initiative in cting, behaving and saying “no” to drugs. This will become a culture in the daily lives of students both at school, at home and in the community. We observed students’ activities of the self- awareness program through “gogok” action. One of the easiest “gosok” actions for students to carry out and to remind them of the dangers of drugs is by shouting anti-drugs. The result of “ sadar bernyali” bsed on “gosok” action program that have been carried out at SLBN 1 Mataram currently show that: students with special needs are able to recognize and understand the dangers of drugs, they brave to refuse and say “no” firmly when offered cigarettes, and are able to take the initiative to reprimand someone who was smoking in the school environment. This “sadar bernyali” that has been running must continue to be carried out repeatedly and continuously so that it becomes a culture in everyday life so that children were accustomed to trying to prevent drug trafficking against themselves both at school and at home. Keywords: “Sadar bernyali” ; “gosok” action ; Children with special Needs ; prevention